Bacillus subtilis Spore Coat - Driks, Adam (American Society for Microbiology, 1999)
In response to starvation, bacilli and clostridia undergo a specialized program of development that results in the production of a highly resistant dormant cell type known as the spore. A proteinacious shell, called the coat, encases the spore and plays a major role in spore survival. The coat is composed of over 25 polypeptide species, organized into several morphologically distinct layers. The mechanisms that guide coat assembly have been largely unknown until recently. We now know that proper formation of the coat relies on the genetic program that guides the synthesis of spore components during development as well as on morphogenetic proteins dedicated to coat assembly. Over 20 structural and morphogenetic genes have been cloned. In this review, we consider the contributions of the known coat and morphogenetic proteins to coat function and assembly. We present a model that describes how morphogenetic proteins direct coat assembly to the specific subcellular site of the nascent spore surface and how they establish the coat layers. We also discuss the importance of posttranslational processing of coat proteins in coat morphogenesis. Finally, we review some of the major outstanding questions in the field.